Sustainability cues in fashion: Practitioners’ and consumers’ perspectives - Branca, G.; Nascimento, J.; Loureiro, S. M. C. (Global Fashion Management Conference Proceeding, 2024)
This research examines the alignment between fashion practitioners’ and consumers’ perceptions of sustainability cues in the fashion industry by employing qualitative techniques. The findings reveal some divergences between their perspectives, underscoring the industry’s challenge in effectively communicating and integrating sustainability into the fashion narrative, to better align with consumer expectations.